A Tunable NIR Filter with Sphere Phase Liquid Crystal - Changli Sun; Jiangang Lu (Crystals, 2019)
A near-infrared (NIR) filter with sphere phase liquid crystal (SPLC) is proposed, which shows a low operating electric field and large temperature-gradient modulations. The central wavelength of the Bragg reflection can be thermally tuned from 1580 nm to 1324 nm with a temperature-gradient of 42.7 nm/K. Meanwhile, the central wavelength can be electrically tuned over 76 nm within a low operating electric field of 0.3 V/μm. Thus, the SPLC filter may achieve a wavelength variation of 256 nm by thermal modulation and 76 nm by electrical modulation. The SPLC filter shows great potential applications in optical communication devices.